Implementasi Konseling Humanistik Bagi Warga Binaan Pengedar Narkoba Lapas Banyuwangi - N, Syakiratun.; Yohandi; Sulaiman, A. Husam (CV. SINAR HOWUHOWU, 2025)
Inmates (specifically in Sritanjung) involved in drug trafficking cases often face a dual stigma: as criminals and as